Pengaruh Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien BPJS di Rumah Sakit Umum Daerah Kabupaten Aceh Besar - Aroni, Defri; Sari, Amelia (Universitas Baiturrahim, 2025)
The quality of health services is one of the key factors in determining the level of patient satisfaction, especially for National Health Insurance (JKN) participants served through the Social Security Organising Agency (BPJS). This study aims to analyse the effect of health service quality on BPJS patient satisfaction at the Regional General Hospital (RSUD) of Aceh Besar Regency. This study uses a quantitative approach with a survey method through a questionnaire distributed to 68 respondents of BPJS patients who receive outpatient services. Service quality variables were analysed through five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The results showed that the quality of service at the Aceh Besar District Hospital was in the Good category at 73.5% and Not Good at 26.5%. Meanwhile, the level of patient satisfaction showed a Satisfied category of 52.9% and Unsatisfied of 47.1%. Further analysis with linear regression showed that all dimensions of service quality had a positive effect on patient satisfaction, with the empathy and assurance dimensions contributing the most. These findings emphasise the importance of improving the quality of interactions and trust in health services for BPJS participants. This study recommends that RSUD Aceh Besar continue to improve service quality, especially in the aspects of communication and personal attention to patients